2018
DOI: 10.1001/jamapediatrics.2017.3879
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of Strategies for Offering Influenza Vaccine in the Pediatric Emergency Department

Abstract: IMPORTANCE Influenza is a significant public health burden, causing morbidity and mortality in children, yet vaccination rates remain low. Vaccination in the pediatric emergency department (PED) setting may be beneficial but, to date, has not been proven to be cost-effective.OBJECTIVE To compare the cost-effectiveness of 4 strategies for PED-based influenza vaccine: offering vaccine to all patients, only to patients younger than 5 years, only to high-risk patients (all ages), or to no patients. DESIGN, SETTING… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 53 publications
(292 reference statements)
0
22
0
Order By: Relevance
“…Despite these obstacles, the program successfully increased vaccination rates without placing a financial burden on the hospital. Hart et al 29 estimated that the net societal cost of offering the vaccine was $103.69 per patient. Our study is unique as our formal cost analysis demonstrated a $22,500 net profit due in part to the zero cost vaccines from the VFC program.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these obstacles, the program successfully increased vaccination rates without placing a financial burden on the hospital. Hart et al 29 estimated that the net societal cost of offering the vaccine was $103.69 per patient. Our study is unique as our formal cost analysis demonstrated a $22,500 net profit due in part to the zero cost vaccines from the VFC program.…”
Section: Discussionmentioning
confidence: 99%
“…This analysis was limited as it did not estimate cost savings from influenza cases averted ($33.51 per case prevented), the cost of possibly wasted vaccines, or the cost of personnel to run the project. 29 This hospital sanctioned influenza vaccination project included an estimated provider and nursing leadership team commitment of 275 staff-hours for planning, collecting, analyzing, and disseminating data, and providing education. This self-sustaining program can be initiated annually by turning on the EHR workflow and re-educating nurses and providers.…”
Section: Discussionmentioning
confidence: 99%
“…37 Measles and influenza vaccination programs have also been implemented in the ED. 36,38 A recent study found that offering influenza vaccine to all eligible pediatric patients in the ED was cost-effective and did not significantly impact patient flow or staffing needs. 38 Interventions examining routine vaccination in acute care settings have shown mixed results but may have some short-term benefit.…”
Section: T a G G E D P Emergency Departments/urgent Care Centerst A Gmentioning
confidence: 99%
“…Health state utilities were assigned a value of 0-1, with 0 equivalent to death and 1 representing perfect health (35). Utility values associated with various outcomes were drawn from the literature (31)(32)(33). 36) When quality-of-life studies were not available for this age group, we used quality-of-life estimates from older populations.…”
mentioning
confidence: 99%